EKSISTENSI PEREMPUAN DALAM KELUARGA (Kajian Peran Perempuan sebagai Jantung Pendidikan Anak) - Dian Lestari (MUWAZAH : jurnal kajian gender, 2016)
This paper discusses about the role of women in the family, which is different from the man, named as daughter, wife and mother. By nature, a woman is given the privilege to pregnancy, childbirth and lactation, thus automatically a woman (mother) has a closeness with children who are born. It allows a woman to be the heart of education for children in developing children's character into a superior generation. The existence of women as educators and forming the character of early childhood, making women more privileged position compared with men.